Deficiency in Neuroserpin Exacerbates CoCl2 Induced Hypoxic Injury in the Zebrafish Model by Increased Oxidative Stress - Han, Sha; Zhang, Dongyang; Dong, Qiang; Wang, Xu; Wang, Liang (Frontiers in Pharmacology, 2021)
Protective strategy against hypoxic-ischemic (H/I) induced injury has been intensively discussed. Neuroserpin, an inhibitor for tissue plasminogen activator (tPA), has been proved a vital neuroprotective agent in cerebral ischemia mouse model and oxygen-glucose deprivation and reoxygenation (OGD/R) cell model. Neuroserpin is a promising therapeutic hint for neonatal hypoxic-ischemia injury. Here, we established a neuroserpin deficient zebrafish to study its role in CoCl2 chemically induced hypoxic injury. CoCl2 exposure was beginning at the embryonic stage. Development defects, neuronal loss, and vascular malformation was assessed by imaging microscopy. Neuroserpin deficient zebrafish showed more development defects, neuronal loss and vascular malformation compared to wide-type. Apoptosis and oxidative stress were evaluated to further identify the possible mechanisms. These findings indicate that neuroserpin could protective against CoCl2 induced hypoxic injury by alleviating oxidative stress.